2018
DOI: 10.1007/s00253-018-9025-2
|View full text |Cite
|
Sign up to set email alerts
|

Integration of ARTP mutagenesis with biosensor-mediated high-throughput screening to improve l-serine yield in Corynebacterium glutamicum

Abstract: L-Serine is widely used in the pharmaceutical, food, and cosmetics industries. Although direct fermentative production of L-serine from sugar in Corynebacterium glutamicum has been achieved, the L-serine yield remains relatively low. In this study, atmospheric and room temperature plasma (ARTP) mutagenesis was used to improve the L-serine yield based on engineered C. glutamicum ΔSSAAI strain. Subsequently, we developed a novel high-throughput screening method using a biosensor constructed based on NCgl0581, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…Similarly, NCgl0581- serE might also be a protein-gene pair sharing the same regulation mechanism. A serine-biosensor based NCgl0581 was reported by Binder et al (30), and based on this study, we constructed a biosensor for L -serine and found that NCgl0581 activated NCgl0580 (SerE) expression in the presence of L -serine, the expression of NCgl0580 enhancing with the L -serine titer increasing (31). However, NCgl0581 did not activate the expression of NCgl0580 in the presence of L -alanine and L -valine.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, NCgl0581- serE might also be a protein-gene pair sharing the same regulation mechanism. A serine-biosensor based NCgl0581 was reported by Binder et al (30), and based on this study, we constructed a biosensor for L -serine and found that NCgl0581 activated NCgl0580 (SerE) expression in the presence of L -serine, the expression of NCgl0580 enhancing with the L -serine titer increasing (31). However, NCgl0581 did not activate the expression of NCgl0580 in the presence of L -alanine and L -valine.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, NCgl0581-serE might also be a protein-gene pair sharing the same regulation mechanism. A serine-biosensor based NCgl0581 was reported by Binder et al [34], and based on this study, we constructed a biosensor for L-serine and found that NCgl0581 activated NCgl0580 (SerE) expression in the presence of L-serine, the expression of SerE enhancing with the L-serine titer increasing [35]. However, NCgl0581 did not activate the expression of SerE in the presence of L-alanine and L-valine.…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, NCgl0581-serE might also be a protein-gene pair sharing the same regulation mechanism. A serine biosensor based NCgl0581 was reported by Binder et al [34], and accordingly, we constructed a biosensor for L-serine and found that NCgl0581 activated NCgl0580 (SerE) expression in the presence of Lserine, with expression of SerE enhancing with increasing L-serine titer [23]. However, NCgl0581 did not activate the expression of SerE in the presence of L-alanine and L-valine.…”
Section: Discussionmentioning
confidence: 75%
“…Subsequently, L-serine exporter serE, serAΔ197, serC and serB were overexpressed in strain A36 to obtainA36-serE-serAΔ197-serC-serB. A36 was stemmed from SSAAI by using ARTP mutation, which produced 34.78 g/L L-serine [23], As shown in Fig. 6, the tandem expression strain A36-serE-serAΔ197-serC-serB shared similar typical growth curves as the parent strain A36 in the overall process.…”
Section: High Yield Production Of L-serine Through Sere Combined Withmentioning
confidence: 88%